Melatonin Related Acneiform Lesions: A Case Report and Potential Mechanism - (:unkn) unknown (AVES, 2021)
Melatonin (MLT) is a hormone secreted by the pineal gland according to the circadian rhythm, which is generated by the suprachiasmatic nucleus. The sleep-promoting effect of exogenous MLT is used to treat steep disorders. The most common side effects reported are headache, somnolence, palpitations, and abdominal pain. Some studies showed dermatological side effects with the use of exogenous MLT, but did not list the specific symptoms. In this article, we describe a case of facial acne occurring after the use of MLT, which is generally known to have protective and healing effects on the skin, and the potential mechanism of this surprising side effect.
Keywords: Acneiform lesions; depression; insomnia; melatonin; sleep disorders; EXOGENOUS MELATONIN; SLEEP; RECEPTORS; INSOMNIA; RELEASE; WOMEN